VOLATILITY CO-MOVEMENT OF ASEAN-5 EQUITY MARKETS - OH, Swee-Ling; LAU, Evan; PUAH, Chin-Hong; MANSOR, Shazali ABU (Journal of Advanced Studies in Finance; Vol 1 No 1 (2010): JASF Volume I Issue 1 Summer 2010, 2010)
Economic cross-linkages and the increased co-movement of asset prices across international markets are important outcomes as the result of globalization. Hereby, the nature of international stock markets and the extent to which the 1997- 1998 East Asian turmoil had affected the market relationship of five countries of Association of Southeast Asian Nations (ASEAN-5) remain as probing questions. Using an array of econometrics analysis upon the stock price volatility series, we found partial market integration for the pre-crisis; whereas in the post-crisis, complete integration prevails. Hence, the financial meltdown in 1997 is said to be a contagion led crisis as markets integrate well off after the crisis than prior to it. Nonetheless, long run portfolio asset diversification benefits across the ASEAN-5 basin are reduced as markets are integrated in both the pre- and post-crisis. As such, the formation of the ASEAN Investment Area (AIA- 1998) parallel with the establishment of a developed ASEAN Index-Financial Times Stock Exchange (FTSE) regional index is viable to foster deeper regional market convergence.